Development, validation and deployment of the EmployABILITY scale. Issue 7 (3rd July 2022) - Bennett, Dawn; Ananthram, Subramaniam
ABSTRACT: This article presents the development, validation and deployment of a scale with which higher education students self-assess their perceived employability. Underpinned by social cognitive career theory and Yorke and Knight's (2007 ) USEM model for students' attainment of employability, a perceived employability questionnaire was developed and piloted with 1849 university students. The final questionnaire was administered with students from over 15 Australian universities, resulting in a sample of 10, 193 students. The scale was validated using exploratory and confirmatory factor analyses, resulting in a 14-factor employability measure that met the acceptable validity thresholds. The multi-factor perceived employability scale validates the USEM model and has implications for theory and practice.